2019
DOI: 10.5603/arm.2019.0049
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Genexpert in the Diagnosis of Tubercular Pleural Effusion in India

Abstract: Introduction: Tubercular pleural effusion is the second most common extrapulmonary form of tuberculosis in India. Developing nations like India face several health challenges and with limited resources, appropriate planning and channelization of the same is the need of the hour. Material and methods: The objective of the study was to determine the role of cartridge-based nucleic acid amplification test (CBNAAT) in the diagnosis of tubercular pleural effusion (TPE) and also to study if any association exists be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…In this study of 100 patients, 80 (80%) are males and 20(20%) females with sex ratio 4:1(M: F). The male predominance seen in our study (80%) is similar to studies done by Modi et al 1 (73.33%), Anushree Chakraborthy et al 8 (76%), Shubham Kumar Sharma et al 11 (78%) and Kate et al 9 (72%). Male predominance is nearer to the study done by Sharma et al The incidence of tuberculosis is more in males due to exposure to outdoor pollution, the presence of confounding factors like smoking, and migration to high prevalent areas.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study of 100 patients, 80 (80%) are males and 20(20%) females with sex ratio 4:1(M: F). The male predominance seen in our study (80%) is similar to studies done by Modi et al 1 (73.33%), Anushree Chakraborthy et al 8 (76%), Shubham Kumar Sharma et al 11 (78%) and Kate et al 9 (72%). Male predominance is nearer to the study done by Sharma et al The incidence of tuberculosis is more in males due to exposure to outdoor pollution, the presence of confounding factors like smoking, and migration to high prevalent areas.…”
Section: Discussionsupporting
confidence: 89%
“…7 2 mL of pleural fluid was collected in a sterile container and was either immediately analyzed or refrigerated at 4 • C and analyzed within two days. An ADA value >40IU/L was taken as a cut off value for diagnosing tubercular effusion 8,9 .…”
Section: Methodsmentioning
confidence: 99%
“…CBNAAT could identify 64 cases (31.2%) from smear negative samples was similar to Dash Manoranjan et al 20 The CBNAAT showed rifampicin sensitivity pattern in concurrent to Vishal Chopra et al 28 Sputum smear was AFB positive in 124 (48%) patients, and CBNAAT detected MTB in 113 (44%) subjects. Among them, 12 had rifampicin resistance similar to Anushree Chakrabortyet al 29 Out of 6.3% were resistant by about were rifamcin resistant LPA, whereas 9.85 were rifampicinresistant by CBNAAT. A total of 209/425 (49%) showed negative for MTB by LPA and 158/425 (37%) showed negative for MTB in CBNAAT which was not in concurrence with Tripathi et al 19 All AFB negative specimens were inoculated on LJ Media, 34 (17%) showed culture positive.…”
Section: Discussionmentioning
confidence: 71%
“…A study by Chakraborty et al selected a total of 75 patients with tuberculous pleural effusion and found that 57 patients were males, showing male predominance. Associated symptoms include cough, chest pain, dyspnea, and fever, while none of them presented with hemoptysis 47 . In addition, the prevalence of MDR‐TB among EPTB is a significant health concern in India.…”
Section: Susceptibility Of Extrapulmonary Tb In South Asiansmentioning
confidence: 99%